2018
DOI: 10.1038/s41598-018-32294-5
|View full text |Cite
|
Sign up to set email alerts
|

Dot-Matrix Hologram Rendering Algorithm and its Validation through Direct Laser Interference Patterning

Abstract: The fight against forgery of valuable items demands efficient and reasonably priced solutions. A security tag featuring holographic elements for anti-counterfeiting is one of them. However, the content and colours of a diffraction image that would be seen by an observer are often counterintuitive in the design stage. Here, we propose an original algorithm based on the conical diffraction formalism, which can be used to describe the variations of a diffraction image with respect to all aspects of observation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Up to irradiation by 27k pulses, the width of the laser‐affected line increases up to two times, whereas further increasing number of pulses width additionally increases only up to 1.2 times. Similar results were obtained for nickel foil ablation with the same setup, where only narrow ridges remained at the maximum energy densities applied, and the Gaussian intensity variation within the irradiated spot was stated to be visible as height modulation …”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Up to irradiation by 27k pulses, the width of the laser‐affected line increases up to two times, whereas further increasing number of pulses width additionally increases only up to 1.2 times. Similar results were obtained for nickel foil ablation with the same setup, where only narrow ridges remained at the maximum energy densities applied, and the Gaussian intensity variation within the irradiated spot was stated to be visible as height modulation …”
Section: Resultssupporting
confidence: 76%
“…The general equation, governing the pitch Λ, is as follows: Λ = λ /(2 n sin θ ), where λ is the wavelength of the laser, n is the refractive index of the surrounding medium (in our case air, n = 1), θ is the incidence angle . More details about the utilized DLIP setup can be found elsewhere . The patterning beam spot size was 75 × 75 μm 2 , and the total patterned area was 4 × 4 arrays of beam size resulting in nearly uniformly patterned areas of 300 × 300 μm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, surface functions including tribological, superhydrophobicity, and bacteria-repellency have been already demonstrated by means of DLIP in previous works [6][7][8]. It was also showed that this technology can be used for decorative applications by forming structural colors on the material surface, including in steels and polymers [9][10][11].…”
Section: Introductionmentioning
confidence: 91%